Experimental infection of some bacterial fish pathogens in the cichlid fish, Oreochromis mossambicus - Omprakasham, M; Manohar, L (Indian Journal of Fisheries, 2011)
Bacterial strains of Pseudomonas fluorescein (NCIB), Pseudomonasfluoresceins (ATCC), Pseudomonas putida (NClB),Escherichia coli (NCIB) and Proteus vulgaris (NCIM) were inoculated into Oreochromis mossambicus through different routes of administration and observed for external and internal pathological changes. The dropsical condition, the typical symptom of bacterial haemorrhagic septicaemia, was observed in only those fish which were injected with Ps.fluorescens through parenteral route of administration, while the scarification method produced variations with the 2 different strains. Ps. putida showed low virulence and pathogenicity. E. coli caused pronounced enteritic conditions. The fish however, did not respond to Pr. vulgaris, by all the 3 routes of administration. The varying degrees of susceptibility is interpreted as due to the strain virulence of the bacterial pathogens tested and the susceptibility of the fish species.